Second to Fourth Digit Ratio (2D:4D) in Female Patients With Systemic Sclerosis: Evidence for Prenatal Androgen Exposure - Akkoc, Ramazan Fazil; Karatas, Ahmet; Oz, Burak (Wiley, 2026)
Objectives Systemic sclerosis (SSc) demonstrates marked female predominance, suggesting hormonal influences in disease pathogenesis. The second-to-fourth digit ratio (2D:4D), a biomarker of prenatal androgen exposure, has been associated with various autoimmune conditions. This study investigated whether 2D:4D ratios differ between female SSc patients and healthy controls. Methods This case-control study enrolled 33 women with SSc (2013 ACR/EULAR criteria) and 30 age-matched healthy female controls. Second and fourth digit lengths were measured bilaterally using digital calipers, and 2D:4D ratios were calculated. Between-group differences were analyzed using Welch's t-test and Mann-Whitney U test. Results SSc patients demonstrated significantly lower 2D:4D ratios than controls bilaterally (right hand: 0.950 +/- 0.029 vs. 1.022 +/- 0.012, p < 0.001; left hand: 0.951 +/- 0.030 vs. 1.022 +/- 0.012, p < 0.001). Effect sizes were substantial (Cohen's d > 2.8). The lower ratios resulted from longer fourth digits rather than shorter second digits, consistent with elevated prenatal androgen exposure. Conclusions Female SSc patients exhibit significantly lower 2D:4D ratios than healthy controls, suggesting higher prenatal testosterone exposure. These findings support the hypothesis that the prenatal hormonal environment may contribute to autoimmune disease susceptibility.
Keywords: 2D:4D; autoimmune disease; prenatal androgen; systemic sclerosis; testosterone